Modelo Log-Burr XII para dados grupados e censurados - Cruz, José Nilton da [UNESP]; Silveira, Liciana Vaz de Arruda [UNESP]; Passos, José Raimundo de Souza [UNESP] (My University, 2012)
Grouped data is a particular case of interval censored, which occur when individuals are assessed at the same time intervals. This type of data, often associated to situations in which the data has a large number ties whose proportions are greater than 25% (Chalita et al., 2002), and can be analyzed considering the discrete time and fitting models to the probability of the individuals enentual failure and the timing of the failure, as he survived the previous interval (Lawless, 1982). The aim of this paper is to propose a model for grouped and censored data based on a more general distribution, log-Burr XII (Silva et al., 2008) and to compare by the corrected Akaike’s Information Criterion (AICc) the fit this model with the generalized log-normal model proposed by Silveira et al. (2010), using a data set related a clinical manifestation of Chaga’s disease, known as chagasic megacolon (Almeida, 1996).

Dados grupados é um caso particular de dados de sobrevivência com censura intervalar, que ocorre quando as observações são avaliadas nos mesmos intervalos de tempo. Este tipo de dados, muitas vezes associa-se às situações em que os dados têm um grande número de empates, ou seja, proporção de empates maior que 25% (Chalita et al., 2002), e podem desta forma ser analisados considerando o tempo discreto e ajustando-se modelos à probabilidade de o indivíduo falhar em um certo intervalo, dado que sobreviveu ao intervalo anterior (Lawless, 1982). Os objetivos deste artigo são propor um modelo para dados grupados e censurados com base numa distribuição mais geral, log-Burr XII (Silva et al., 2008), e comparar pelo Critérios de Informação de Akaike Corrigido (AICc) e Critério de Informação Bayesiano o ajuste deste modelo com o modelo lognormal generalizada proposto por Silveira et al. (2010), utilizando um conjunto de dados referente a uma manifestação clínica da doença de Chagas, conhecida como megacolo chagásico (Almeida, 1996).
Log-Burr XII model for grouped and censored data
Keywords: Generalized log-normal model; Discrete models; Interval censored; AICc; Chagas’disease; Chagasic megacolon; Modelo log-normal generalizada; Modelos discretos; Censura intervalar; AICc; Doen ça de Chagas; Megacolo chag asico